Fluid mechanics of viscoplasticity - Huilgol, R. R. 1939-; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2015)
In this book, we shall consider the kinematics and dynamics of the flows of fluids exhibiting a yield stress. To highlight the principal characteristics of such fluids, the first chapter emphasizes the role played by the yield stress. Next, a careful description of the continuum mechanics behind the constitutive equations for incompressible and compressible viscoplastic fluids is given in Chapters 2?4. In Chapters 5 and 6 analytical solutions to several steady and unsteady flows of Bingham fluids are presented. The subsequent Chapters 7?10 are concerned with the development of variational principles and their numerical solutions, along with perturbation methods which play a significant role in numerical simulations.
The Basic Features of Viscoplasticity -- Kinematics of Fluid Flow -- Fundamental Equations -- Constitutive Equations -- Analytic Solutions: Steady Flows -- Analytic Solutions: Unsteady Shearing Flows -- Analytical Approximation Techniques -- Variational Principles and Variational Inequalities -- Energy Methods in Action: Equality, Inequality and Stability -- Numerical Modelling.
Electronic reproduction.
Keywords: Fluid mechanics; Viscoplasticity; Electronic books